2022
DOI: 10.14202/vetworld.2022.1221-1227
|View full text |Cite
|
Sign up to set email alerts
|

The first study on the seroprevalence of Anaplasma spp. in small ruminants and assessment of associated risk factors in North Egypt

Abstract: Background and Aim: Ovine anaplasmosis is a rickettsial disease caused by Anaplasma spp. These Gram-negative intracellular bacteria are mainly transmitted by ticks and infected blood cells of caprine, ovine, and wild small ruminants. At present, epidemiological data on anaplasmosis in cattle, dogs, and camels in Egypt are available, but the data about Anaplasma spp. in sheep and goat are scarce. This study aimed to determine the seroprevalence of Anaplasma spp. in small ruminants and assess the associated risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Similarly, the prevalence of anaplasmosis was significantly higher in goats than in sheep, regardless of the study area. These findings are in agreement with previous research by Selim et al [22], Yousefi et al [40], and Enkhtaivan et al [49], as they demonstrated higher infection rates in goats (71.3%, 21.3%, and 34.7%, respectively) compared to sheep (69%, 18.3%, and 20.8%, respectively). There is a local trend of rearing goats with cows by resource-limited smallholder dairy farmers in Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the prevalence of anaplasmosis was significantly higher in goats than in sheep, regardless of the study area. These findings are in agreement with previous research by Selim et al [22], Yousefi et al [40], and Enkhtaivan et al [49], as they demonstrated higher infection rates in goats (71.3%, 21.3%, and 34.7%, respectively) compared to sheep (69%, 18.3%, and 20.8%, respectively). There is a local trend of rearing goats with cows by resource-limited smallholder dairy farmers in Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…In this study conducted in Egypt’s Luxor province, the rate of A. ovis infection in goats was 33.33%, which is higher than those detected by ELISA in goats in other Egyptian provinces, specifically in Alexandria (23.3%), Behirah (13.8%), Kafr El-Sheikh (22.6%), and El Gharbia (25%) [ 59 ].…”
Section: Discussionmentioning
confidence: 95%